2020
DOI: 10.1038/s41598-020-72638-8
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of metabolic pathways by carnitine palmitoyl-transferase 1 plays a key role in central nervous system disorders: experimental evidence based on animal models

Abstract: The etiology of CNS diseases including multiple sclerosis, Parkinson’s disease and amyotrophic lateral sclerosis remains elusive despite decades of research resulting in treatments with only symptomatic effects. In this study, we provide evidence that a metabolic shift from glucose to lipid is a key mechanism in neurodegeneration. We show that, by downregulating the metabolism of lipids through the key molecule carnitine palmitoyl transferase 1 (CPT1), it is possible to reverse or slowdown disease progression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 120 publications
3
20
0
Order By: Relevance
“…Taken together, these data suggest that disease progression is influenced by a modulation of lipid β-oxidation, involving CS in the translocation of FAs to mitochondria. Since CPT1 plays a key role in mitochondrial processes, many studies have targeted its pharmacological or genetic inhibition [ 52 , 53 , 54 ] to show that the shift from glucose to lipid metabolism is crucial for disease development. Metabolic deregulation has been proposed as a crucial point in the pathogenesis of several neurodegenerative diseases, such as ALS [ 55 ], myotonic dystrophy [ 56 ], Alzheimer’s, and Parkinson’s diseases [ 57 ], where the balance between glucose and lipid oxidation is disturbed, as is the case in HD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, these data suggest that disease progression is influenced by a modulation of lipid β-oxidation, involving CS in the translocation of FAs to mitochondria. Since CPT1 plays a key role in mitochondrial processes, many studies have targeted its pharmacological or genetic inhibition [ 52 , 53 , 54 ] to show that the shift from glucose to lipid metabolism is crucial for disease development. Metabolic deregulation has been proposed as a crucial point in the pathogenesis of several neurodegenerative diseases, such as ALS [ 55 ], myotonic dystrophy [ 56 ], Alzheimer’s, and Parkinson’s diseases [ 57 ], where the balance between glucose and lipid oxidation is disturbed, as is the case in HD.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic deregulation has been proposed as a crucial point in the pathogenesis of several neurodegenerative diseases, such as ALS [ 55 ], myotonic dystrophy [ 56 ], Alzheimer’s, and Parkinson’s diseases [ 57 ], where the balance between glucose and lipid oxidation is disturbed, as is the case in HD. For HD, enhanced lipid β-oxidation leads to an increase in radical oxygen species and oxidative stress, resulting in defective respiratory chains and ATP deficit [ 39 ], which further drives metabolic deregulation and mitochondrial damage on the one hand, and triggers neurodegeneration on the other [ 49 , 52 ]. Many CPTs and carnitine transporter inhibitors have been tested to target metabolic deregulation in neurological diseases [ 14 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Counterintuitively, mice with a specific mutation in CPT1A , which is associated with low susceptibility to MS in the Inuit population and reduced CPTa1 activity, have reduced disease severity in EAE compared to wild-type mice 204 . Inhibiting FAO via etomoxir reduced CNS inflammation and demyelination in EAE 205 , 206 , indicating that overall reduction of CPT1A activity (and consequently FAO) can ameliorate neuroinflammation.…”
Section: Is Multiple Sclerosis a Metabolic Disease?mentioning
confidence: 94%
“…In addition, Taib et al [ 77 ] observed the significant inhibition of cell proliferation when etomoxir was applied alongside oleic acid in GBM and astrocytic cells [ 77 ]. To date, most studies in this area have employed in vitro experiments using gliomas or other cancer cells; however, the literature also contains clinical trials and animal studies demonstrating the inhibitory effects of etomoxir treatment in neurodegenerative diseases, such as Parkinson’s or Alzheimer’s disease [ 78 ]. Thus, we can assume that BBB crossing is an issue that can be overcome in the case of etomoxir and that more trials examining the use of this drug to treat gliomas are forthcoming.…”
Section: Carnitine Palmitoyl Transferase-1a (Cpt-1a)-inhibitor—etomoxirmentioning
confidence: 99%